A Cadaveric Study on the Prevalence of Hartmann Pouch of Gallbladder with Relation to Gallstones in Basrah City - Nawal M Abdullah1, Abdul Kareem Q Mohamed2, Sameh S Akkila3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hartmann pouch is a dilatation of the wall of the gallbladder at the region between neck and the cystic duct, It is inconstant feature found as an anatomical variant and considered a frequent site for gall stone impaction and mucocele formation as a complication . Knowledge about anatomy of the pouch is important while performing surgery for cholecystectomy to avoid serious complications.Objective: To identify the incidence and nature of Hartmann’s pouch in human gallbladder and the relation with gallstones for the growing importance and use of various invasive surgical techniques for gallbladder and extrahepatic biliary diseases.Material and Method: The study was carried out in the department of Forensic Medicine at Basrah city ,from Jan 2018 to Jan 2019 .Two hundred fourteen gallbladders were obtained from cadavers that were under examination in the morgue , The gallbladders were examined morphologically to show Hartman pouch and gall stone existence and biopsies from the pouch were taken for histopathological examination.Results: In the present study Hartman pouch was found in 4.7%, usually at older age group (? 40 yrs.). It was slightly higher in male than female and no significant association between Hartman pouch and gall stone presence. Histological picture showed normal histology of the three layers as seen in normal gallbladderConclusion: Hartman pouch is inconstant feature, more in male with no significant relation to gall stone, exist as an anatomical entity in our area of study